Trastuzumab deruxtecan in recurrent uterine serous carcinoma resistant to trastuzmab based-chemotherapy - Blair McNamara; Stefania Bellone; Cem Demirkiran; Tobias Max Philipp Hartwich; Alessandro D. Santin (Elsevier, 2023)
Background: Treatment of uterine serous carcinoma (USC) is challenging; effective treatment options for metastatic and recurrent disease are needed. Case: A 68-year-old woman with recurrent, metastatic, USC overexpressing HER2/neu experienced durable response to the antibody drug conjugate (ADC) trastuzumab-deruxtecan (T-DXd), after failing multiple standard and experimental treatments targeting HER2/neu. She experienced a significant reduction in disease burden, disappearance of metastatic back bone pain as well as normalization of CA-125 quickly after starting treatment. Her disease continued to show response to treatment over 5 months and 7 cycles of T-DXd therapy. She did not experience any dose-limiting side effects and tolerated treatment with 5.4 mg/kg T-DXd without issue. Conclusion: T-DXd may present a new treatment option for chemotherapy-resistant uterine serous carcinoma.